2013
DOI: 10.4236/fns.2013.42028
|View full text |Cite
|
Sign up to set email alerts
|

Back to Basics: Estimating Protein Requirements for Adult Hospital Patients. A Systematic Review of Randomised Controlled Trials

Abstract: Aim: To review the supporting evidence for protein requirements in hospitalised adults, and compare the findings with commonly-used guidelines and resources. Methods: a systematic review was conducted based on a computerised bibliographic search of MEDLINE, EMBASE and CINAHL from 1950 to October 2011, as well as a citation review of relevant articles and guidelines. Studies were included if they were randomised clinical trials in hospitalised or chronically ill adults, comparing two or more different levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Accordingly, the intervention group approached what current international guidelines recommend, and the comparator group represents "usual" clinical care, as established in numerous observational trials in various regions. Three systematic reviews have previously evaluated the impact of protein provision in the critically ill. 20,22,42 The most recent of these was by Davies et al, 20 who evaluated the effect of 2 different protein doses on mortality, length of stay, incidence of pneumonia, and length of mechanical ventilation. Similar to the current review, they reported that greater protein provision did not appear to influence mortality or any of the other secondary outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, the intervention group approached what current international guidelines recommend, and the comparator group represents "usual" clinical care, as established in numerous observational trials in various regions. Three systematic reviews have previously evaluated the impact of protein provision in the critically ill. 20,22,42 The most recent of these was by Davies et al, 20 who evaluated the effect of 2 different protein doses on mortality, length of stay, incidence of pneumonia, and length of mechanical ventilation. Similar to the current review, they reported that greater protein provision did not appear to influence mortality or any of the other secondary outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 8 studies included by Davies et al that delivered predominately EN, [44][45][46][47][48][49][50][51] none of these achieved ࣙ1.2 g/kg per day protein in the intervention group (ie, international guideline recommendations) and <1.2 g/kg per day in the comparator group. Furthermore, there have been trials recently published in this field, with 4 out of the 6 studies included in the current systematic review published after the review by Davies et al 20 The 2 systematic reviews conducted prior to Davies et al 22,42 also incorporated both EN and PN and multiple study methodologies. In addition, Ferrie et al included studies that were not conducted in the ICU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…103 This means that a higher total energy intake is required to maintain body weight when the diet is extremely high in protein. 104 …”
Section: Effect Of Energy Balance On Protein Requirementsmentioning
confidence: 97%
“…104 Table 6 summarizes current international guidelines for protein requirements. A recent review concluded that the most effective energy to protein ratio for critically ill patients remains unknown.…”
Section: Determining Protein Requirementsmentioning
confidence: 99%